Antibiotic ciprofloxacin removal from aqueous solutions by electrochemically activated persulfate process: Optimization, degradation pathways, and toxicology assessment - Yakamercan, Elif; Aygun, Ahmet; Simsek, Halis (Science Press, 2024)
Ciprofloxacin (CIP) is a commonly used antibiotic in the fluoroquinolone group and is widely used in medical and veterinary medicine disciplines to treat bacterial infections. When CIP is discharged into the sewage system, it cannot be removed by a conventional wastewater treatment plant because of its recalcitrant characteristics. In this study, boron-doped diamond anode and persulfate were used to degrade CIP in an aquatic solution by creating an electrochemically activated persulfate (EAP) process. Iron was added to the system as a coactivator and the process was called EAP + Fe. The effects of independent variables, including pH, Fe2 + , persulfate concentration, and electrolysis time on the system were optimized using the response surface methodology. The results showed that the EAP + Fe process removed 94% of CIP under the following optimum conditions: A pH of 3, persulfate/Fe2 + concentration of 0.4 mmol/L, initial CIP concentration 30 mg/L, and electrolysis time of 12.64 min. CIP removal efficiency was increased from 65.10% to 94.35% by adding Fe2 + as a transition metal. CIP degradation products, 7 pathways, and 78 intermediates of CIP were studied, and three of those intermediates ( m/z 298, 498, and 505) were reported. The toxicological analysis based on toxicity estimation software results indicated that some degradation products of CIP were toxic to targeted animals, including fathead minnow, Daphnia magna , Tetrahymena pyriformis , and rats. The optimum operation costs were similar in EAP and EAP + Fe processes, approximately 0.54 euro/m3 . (c) 2024 The Research Center for Eco-Environmental Sciences, Chinese Academy of Sciences. Published by Elsevier B.V.
Keywords: Ciprofloxacin; Response surface methodology; Electrochemically activated; persulfate; Electrooxidation